Analisis Kinerja Sistem Pembangkit Listrik Industri Pabrik Kelapa Sawit Di PT Palem Segar Lestari Desa Tepian Nunukan Barat Kabupaten Nunukan Kalimantan Utara - Andri Supriadi; Dino Erivianto; Siti Anisah (CV. Hawari, 2026)
Palm oil mills produce biomass in the form of fibre and shells that have the potential to be utilised as an energy source for internal power generation. This study aims to analyse the performance of the biomass-based power generation system at the PT Palem Segar Lestari Palm Oil Mill in terms of generator capacity suitability, energy efficiency, and operational stability. The research method used is a descriptive quantitative approach through the measurement of operational parameters and technical performance analysis based on thermodynamic principles and energy balance. The analysis was conducted on the mill's processing capacity, process steam requirements, biomass heat energy, boiler steam production, and steam turbine power. The results showed that at an operating capacity of around 45 tonnes of fresh fruit bunches per hour, the minimum steam requirement reached ±27,000 kg/hour, and the power generation system was capable of producing electricity according to the mill's needs with an electricity consumption intensity of 15–17 kW/tonne of fresh fruit bunches. Overall, the biomass power generation system at PT Palem Segar Lestari demonstrates effective performance in supporting independent factory operations with potential for optimisation in fuel management and boiler efficiency.